Radiographic study of tibiotalar alignment in normal ankles - Costa Benevides, Pedro; Marques De Medeiros, Caled; Jardim Fairbanks, Paula; Augusto de Souza Nery, Caio; Marion Alloza, José Felipe; Leme Godoy-Santos, Alexandre; Sanches de Oliveira Júnior, Adilson; Brauer Bonjardim de Souza, Glenda; Do Amaral Masagão, Renato; Pires Prado, Marcelo (Journal of the Foot & Ankle, 2025)
Objective: Establish reference values for radiographic ankle measurements in healthy individuals. With these data, it will be possible to identify deviations from normality and assist in diagnosing and treating ankle osteoarthritis. Methods: One hundred and fifty-six standard digital radiographs in physiological position with ankle weight-bearing in the anteroposterior (AP) and lateral incidences of 111 patients were evaluated. The parameters included in the AP incidence are the distal tibial articular surface angle, the talar tilt, and the talus center migration. The parameters in the lateral incidence are the sagittal distal tibial angle and the lateral position of the talus. Radiographic measurements were performed through inter- and intraobserver agreement, which was considered to have a significance level of 5%. Results: There was good agreement between the measurements performed by different observers, establishing the reference values for each parameter. Conclusion: All radiographic parameters tested showed excellent or good correlations to evaluate ankle alignment and should be considered together for a complete and adequate evaluation. Level of Evidence IV; Therapeutic Studies; Case Series.